Efecto de variación de temperatura de trabajo en las curvas características de una bomba centrífuga. - Alvarado Alvarado, Victor Manuel (2020)
In the present research work is proposed to analyze the effect of temperature variation of the working fluid on the characteristic curves of a centrifugal pump of ½ Hp brand Pedrollo CPm130. In the development of the document, the methodology used for data acquisition is detailed, and information regarding the influence that the temperature of the fluid has on a centrifugal pump was systematized by means of books, magazines, articles, etc. Based on this information, the necessary components that the test bench should have were determined. A practice guide was prepared based on the institutional format of the National University of Loja (UNL) and standard ISO 9906:1999, which facilitated the acquisition of data by means of the record sheet prepared from the above, which gave way to the analysis of characteristic curves where it was found that the increase in water temperature influences the operation of the pump; affecting the delivered flow, height and performance. Three experimental designs were made for the characteristic curves Three experimental designs were made for the characteristic curves of the Pedrollo CPm130 pump, obtaining three mathematical models that it relates: Flow-Height (Q-Hman), Flow-Power electric (Q-Pe), Flow-Motorpump performance (Q-n); for which the number of factors and levels of each one were determined and with the help of specialized software, it was possible to obtain the mathematical models that respond to the variables of Height , Power and Performance.